Sistem Informasi Persediaan Barang Pada UMKM Reseller Barang Pokok - Aswar Hanif; Hanif, Aswar; Wahyudi, Endang; Adianto, Harna; Martanto, Lilik (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2022)
Abstracts - Inventory is a representation of a revenue source, and in its application, it can help a business in dealing with fluctuations in demands and reduce the cost of purchasing goods. Inventory management systems can reduce slow data processing, reduce the risk of errors in recording, and generate reports quickly. CV. WU is an MSME reseller engaged in trading of basic goods. In managing its inventory, common problems such as recording incoming goods, outgoing goods, and monitoring the number of goods in storage, are still handled in a conventional way. This slows down the work process and complicates decision making for purchasing inventory. Using the Waterfall Model, a web-based inventory management system was developed for CV. WU. The server-side operations are implemented using the Django web framework, and the client-side operations are built leveraging the Bootstrap framework. The final result of the developed system met the specified requirements. Inventory management on CV. WU becomes easier and more efficient, by storing incoming and outgoing goods records in a database. The process of monitoring the inventory of goods becomes faster, because the system calculates the data automatically. The ease of producing reports is expected to benefit management in the process of decision making regarding inventory purchases.